Cultural Keystone Places and the Chumash Landscapes of Kumqaq', Point Conception, California. Issue 3 (July 2022) - Rick, Torben C.; Braje, Todd J.; Graham, Lain; Easterday, Kelly; Hofman, Courtney A.; Holguin, Brian E.; Mychajliw, Alexis M.; Reeder-Myers, Leslie A.; Reynolds, Mark D.
Abstract : The places in which people live and spend time are steeped in history, memory, and meaning from the intersection of daily life, environmental interactions, cultural practices, and ritual. Geologic features, plants, animals, and ecosystems merge with these cultural histories, forming critical parts of the landscape and areas of "high cultural salience, " or "cultural keystone places" (CKPs). We identify Kumqaq' (Point Conception) and the surrounding area in California as a Chumash CKP. Ethnohistoric accounts and contemporary Chumash community members have long demonstrated the importance of Point Conception in Chumash worldview and identity, whereas biologists, ecologists, and conservationists reference the area's rich biodiversity and significance as a biogeographical boundary. Recent archaeological survey of the coastline surrounding Kumqaq' highlights these connections, identifying over 50 archaeological sites—including shell middens, villages, lithic scatters, and rock art—with at least 9, 000 years of occupation. Ongoing collaborations among archaeologists, the Nature Conservancy, and Chumash community members help document and understand the long-term linkages between cultural and biological diversity and how integrating these perspectives can help ensure the resilience of this nexus of human and natural history in the Anthropocene future.